2019
DOI: 10.1021/acs.jpcc.8b11983
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of the Relation between Analyte Retention and Surface Diffusion in Reversed-Phase Liquid Chromatography

Abstract: In reversed-phase liquid chromatography (RPLC), analyte molecules retained on the hydrophobic stationary phase can undergo fast surface diffusion within an acetonitrile (ACN)-rich border layer between the stationary phase and the water (W)–ACN mobile phase. We perform molecular dynamics simulations in an RPLC mesopore model employing an endcapped C18 phase to determine retention and diffusive mobility data for four analytes at solvent ratios between 80/20 and 10/90 (v/v) W/ACN. Simulated retention data are val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(137 citation statements)
references
References 54 publications
6
131
0
Order By: Relevance
“…While we primarily focus on applications in heterogeneous catalysis and adsorption based separations, the fundamental concepts of molecular diffusion have broader application to membrane science [12], chromatography [13], gas exploration [14], environmental remediation [15], etc. Greater cross-community collaborations can help provide new insights into diffusion processes that are valuable across disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…While we primarily focus on applications in heterogeneous catalysis and adsorption based separations, the fundamental concepts of molecular diffusion have broader application to membrane science [12], chromatography [13], gas exploration [14], environmental remediation [15], etc. Greater cross-community collaborations can help provide new insights into diffusion processes that are valuable across disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…As of version 0.2.0, only the structure of β-cristobalite SiO 2 has been implemented. Simulations in slit-pore models have proved that the faces of β-cristobalite SiO 2 , particularly its (111) face, support the envisioned ligand density and residual hydroxylation of functionalised and bare silica materials used in chromatographic columns [10,[12][13][14]24,25,34,40,41]. Moreover, MD simulations have shown that non-functionalised, cylindrical pores carved from β-cristobalite SiO 2 replicate the relevant properties of the bare silica surface in liquid chromatography well [9,11].…”
Section: Pore Generationmentioning
confidence: 75%
“…The specific length required depends on the system studied (the properties of the functionalised silica as well as of the solvent mixture). The solvent reservoir length chosen for this example was informed by prior MD simulation studies using a slit-pore model of C 18 functionalised silica equilibrated with water-acetonitrile mixtures [24,25]. The chosen length should suffice for modelling bonded phases of similar or shorter chain length than C 18 and common aqueousorganic mobile phases.…”
Section: Pore Model For Reversed-phase Liquid Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, a fair approximation of a mean value of the phase ratio φ over the used temperature interval can be considered as 0.25. 22,23 With this value the formula of calculating the standard entropy variation becomes: ΔS 0 = 19.15 x (a' + 0.602). The values resulted from these calculation are given in Table 3.…”
Section: Resultsmentioning
confidence: 99%